Development and Validation of an Instrument for the Measurement of Religious Coping Strategies - González-Rivera, Juan Aníbal; Pagán-Torres, Orlando M.; González-Rivera, Juan Aníbal; Pagán-Torres, Orlando M. (Instituto de Investigaciones Psicológicas (IIPSI, Conicet-UNC), 2018)
This article examines the psychometric properties of the Religious Coping Strategies Inventory (IEAR) in a sample of Puerto Rican adults. Religious coping methods are ways of understanding and dealing with negative life events that are related to the sacred. A total of 350 Puerto Ricans participated in this exploratory and psychometric study. The results indicated that the scale has a two-factor structure. These factors were denominated internal strategies and external strategies. A total of 12 items complied with the criteria of discrimination and presented appropriate factorial loads (six items per factor). The reliability index of the scale was of .95 (Cronbach’s alpha). These results suggest that the IEAR has the potential to measure this construct among Puerto Rican adults. Likewise, the IEAR will advance further research of religious coping in Puerto Rico and Latin America.